Perlindungan Hukum Terhadap Penerima Hak dalam Perjanjian Waralaba di Indonesia - I Made Dwi Wahyu Kartika; Ni Made Jaya Senastri; Ni Gusti ketut Sri Astiti (Warmadewa Press, 2021)
Franchising is a marketing concept in order to expand the business to support the economy, in this case there are often problems related to the agreement that has been set. Therefore, a legal protection is needed for the recipient of the right. The purpose of this study is to reveal the choice of agreement in the implementation of franchise agreements in Indonesia and the form of legal protection for franchisees in Indonesia. The research method in this study is normative research focusing on the behavior of the legal community and through legal science book references. Sources of data used are primary data by examining regulations related to franchises and secondary data by examining literature, books, papers and journals. Data collection techniques by classifying primary legal materials with secondary legal materials as a support. Analysis of Legal Materials obtained by qualitative analysis. The results of the study reveal that the franchise business in Indonesia has been regulated in the provisions of PP No. 42 of 2007 concerning franchising, for the legal requirements for the establishment of a franchise business, it must meet the provisions in Article 1320 of the Civil Code, and the form of legal protection for franchisees is contained in Article 7 of the Regulation of the Minister of Trade Number 12/ MDAG/Per/3/2006 so the franchisor cannot terminate the agreement at any time or at any time.